Respuesta :
Answer:
Your solution is (6, -7)
Step-by-step explanation:
4x + 2y = 10
x - y = 13
We want to solve for one variable at a time.
Let's start with x.
x - y = 13
Add y to both sides.
x = 13 + y
Now we have an expression for x.
Plug this into each instance of x in the first equation.
4x + 2y = 10
4(13 + y) + 2y = 10
Distribute the 4 across the parentheses.
52 + 4y + 2y = 10
Combine like terms.
52 + 6y = 10
Subtract 52 form both sides.
6y = -42
Divide both sides by 6.
y = -7
Now that we know y, plug its value back into the expression for x.
x = 13 + y
x = 13 + (-7)
Simplify.
x = 13 - 7
Subtract.
x = 6
Your solution is (6, -7).
Hope this helps!